Museums as Disseminators of Niche Knowledge: Universality in Accessibility for All - Rizzo, Alessandra (Journal of Audiovisual Translation, 2019)
Accessibility has been facing several challenges within Audiovisual Translation Studies and has also gained great opportunities for its establishment as a methodologically and theoretically well-founded discipline. Audiovisual translation modes have achieved a crucial role in the transmission of what scholarly studies have discussed in relation to media accessibility as a set of services and practices providing access to audiovisual media content for persons with sensory impairment. Today accessibility has become a concept involving more and more universality, since it is extensively contributing to the dissemination of audiovisual and visual products about issues on minorities, and also addressing all human beings, regardless of cultural and social differences. Against this theoretical backdrop, accessibility is scrutinised within the context of aesthetics of marginalisation, migration, and minorities as modalities which encourage the diffusion of ‘niche’ knowledge, and as universal processes of translation and interpretation that provide access to all knowledge as counter discourse. Within this framework, the ways in which language is used can be considered the beginning of a type of local grammar for interlingual translation and subtitling applied to museum contexts of marginalisation, migration and minorities. Drawing upon well-established research in the field of audiovisual translation and media accessibility, and by adopting systemic-functional and lexical-semantic methodological approaches for translation quality assessment of museum text types, this study aims to put emphasis on accessibility as a societal instrument that contributes to giving voice to minorities through knowledge dissemination in English as a lingua franca by means of aesthetic narrative types within the field of the visual arts (i.e. museum settings). In this sense, accessibility is viewed as the embodiment of universality that ensures universal access to knowledge for all citizens as a human rights principle, while acting as an agent for the democratisation and transparency of information against media discourse distortions and oversimplifications.